Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Batu Bata Merah di Wailiti Kecamatan Alok Barat - Helena Elviana; Nur Chotimah; Amir Djonu (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research aims to determine the effect of product quality on purchasing decisions of red bricks in Wailiti, Alok Barat District. The population in this research are consumers of TONI PUTRA's red brick owned by Mr. Antonius Gebang located in the Wailiti sub-district, Alok Barat District. The sample in this research is 96 people. The technique used in this study is the Random Sampling Technique. This research uses descriptive method and quantitative approach. The results of this study indicate that the influence of the independent variable product quality has a positive and significant effect on purchasing decisions, which means that h1 is accepted and h0 is rejected. Based on the results of simple linear regression calculations, it is obtained Purchase Decision = 6.199 + 0.417 (Product Quality). Testing the hypothesis from the calculation of the t test results obtained t count> t table 9.641> 1.6601, which means that h0 is rejected and h1 is accepted. The results show that the coefficient of determination (R square) of the independent variable on the dependent variable is R2 = 0.497 or 49.7%.